2022
DOI: 10.3390/ma15051933
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Retention, Wear, and Maintenance of Attachment Systems for Single- or Two-Implant-Retained Mandibular Overdentures: A Systematic Review

Abstract: Attachment systems (AS) enhance retention and stability by anchoring the overdentures to implants. Since 2002, the McGill consensus statement recommends the 2-implant-retained overdentures as the standard choice for edentulous mandible (2-IRMO). Considering the large number of AS available, it remains difficult for a practitioner to make a reasoned choice. A systematic review was conducted in PubMed/Medline and carried out independently by three authors, on retention, wear, and maintenance of AS used clinicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 42 publications
0
24
0
Order By: Relevance
“…Greater retentive strength may also affect the longevity of the flexible matrix [ 6 9 ]. Maximum studies evaluated the retentive strengths of 2IMO after simulated function and very few evaluated the stresses at baseline without age simulation [ 9 , 11 15 ]. The attachments are serviceable from the first day of their usage in mouth; hence, the present study evaluated their retentive strength without any age simulation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Greater retentive strength may also affect the longevity of the flexible matrix [ 6 9 ]. Maximum studies evaluated the retentive strengths of 2IMO after simulated function and very few evaluated the stresses at baseline without age simulation [ 9 , 11 15 ]. The attachments are serviceable from the first day of their usage in mouth; hence, the present study evaluated their retentive strength without any age simulation.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies are advocated using different retentive elements like PEEK and polyvinyl siloxane. Wakam et al [ 15 ] carried out systematic review of 14 clinical and 31 in vitro studies regarding the retention, wear, and maintenance of attachments used clinically or in vitro specifically for 1IMO or 2IMO. They have concluded that the plastic retention devices wear out faster and more significantly than metal ones.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The costs for making an overdenture remain slightly below average when compared to an implant-supported fixed complete denture, however, the maintenance of an overdenture can occur on average after 12 months of prosthesis installation, and the main problems related to it are the loss of retention due to wear of the retention systems of the prosthesis (Wakam et al 2022).…”
Section: )mentioning
confidence: 99%